Six years of fruit production by mahogany trees (Swietenia macrophylla King): patterns of variation and implications for sustainability - Snook, Laura K.; Camara-Cabrales, L.; Kelty, M.J. (2005)
Although mahogany, the most commercially important timber tree in Neotropical forests, is widely acknowledged to be threatened by unsustainable logging which does not provide for its regeneration, its fruiting dynamics are poorly understood. During each of six successive years, the authors measured tree diameters and counted woody fruit capsule segments that fell below the crowns of 82 mahogany trees in natural forest in central Quintana Roo, Mexico. Sample trees ranged from <20 cm to more than 100 cm DBH. Fruit production increased with diameter, and trees 75 cm produced significantly more fruits each year than did trees of smaller diameters. Large trees could produce more than 700 fruits/year. Trees 75 cm DBH were also more consistent producers: while up to 27% of trees <75 cm DBH produced <1 fruit/year in any year, at least 93% of larger trees produced fruit every year. Over the 6 years, individual trees 75 cm produced a total of 367 34 fruits, as compared to 91 8 fruits among trees <75 cm (an average of 61 7 and 15 2 fruits/year, respectively). However, the number of fruit produced per unit crown volume was not significantly different between the two size categories. Fruit production varied among years, with the highest production in 1998 and the lowest in 1999 and 2000. The population of sampled mahogany trees produced approximately three times more fruit, and individual trees produced up to five times more fruit, in the year of highest production, as compared to the lowest. Mahogany does not exhibit the fruit production patterns found in mast fruiting species. Inter-annual variability in size of fruit crops at both the population and individual-tree levels are lower than in masting species, and the synchronocity among trees was low. Basal area growth averaged 76.5 18.6 cm2/year for trees 75 cm and 29.9 1.7 cm2/year for trees <75 cm DBH, and varied significantly among years. Years of high fruit production were also years of good growth, implying ‘‘resource matching’’ rather than the ‘‘resource switching’’ associated with masting. To ensure seed production for the regeneration of mahogany it is important to retain mahogany trees 75 cm DBH as seed sources. This presents a challenge, since currently mahogany trees in this region are harvested down to a minimum diameter as low as 55 cm.